1975
DOI: 10.1113/jphysiol.1975.sp010841
|View full text |Cite
|
Sign up to set email alerts
|

The volume and energy content of meals as determinants of gastric emptying.

Abstract: SUMMARY1. Results were collected from thirty-three published and unpublished studies of gastric emptying. The volumes of the meals ranged from 50 to 1250 ml., and composition varied from pure carbohydrates to ordinary food.2. From the published composition of the meals, their nutritive density, as kcal/ml. (4.18 KJ/ml.) was computed: it ranged from zero to 2-3 kcal/ml.3. The volume of each meal, or test meal, delivered to the duodenum in 30 min was determined, assuming that gastric emptying was exponential.4. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
276
5
7

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(302 citation statements)
references
References 23 publications
14
276
5
7
Order By: Relevance
“…103,104 The implication is that eating energy dense foods (for example, high fat foods) may not allow gastric distension to contribute sufficiently to satiety. As a result of this, the energy density of foods may be an important factor that influences how much energy is consumed in a meal.…”
Section: Food Palatabilitymentioning
confidence: 99%
“…103,104 The implication is that eating energy dense foods (for example, high fat foods) may not allow gastric distension to contribute sufficiently to satiety. As a result of this, the energy density of foods may be an important factor that influences how much energy is consumed in a meal.…”
Section: Food Palatabilitymentioning
confidence: 99%
“…Gastric emptying can be affected by intragastric volume (20), which varies in mouse strains of different size. The smaller CAST mice consumed 32% less of the test meal than B6 mice but also had 32% lower stomach mass.…”
Section: Gene Expression Candidates In Stomachmentioning
confidence: 99%
“…Several authors have indicated that satiation may be controlled by the weight of previously consumed foods (McHugh & Moran, 1979;Hunt & Stubbs, 1994). There are two important methodologic differences between these studies and our study.…”
Section: Discussionmentioning
confidence: 68%
“…Studies investigating the effect of food volume consumed in one meal on subsequent energy intake, suggest that high volume intakes produce a lower gastric emptying rate, and consequently increase satiety (McHugh & Moran, 1979;Hunt & Stubbs, 1994). However, these hypotheses have not been tested on preschool children.…”
Section: Introductionmentioning
confidence: 99%